PENINGKATAN KEMAMPUAN REPRESENTASI MATEMATIS SISWA SMP MELALUI PEMBELAJARAN METAKOGNITIF DAN PEMBELAJARAN METAKOGNITIF BERBASIS SOFT SKILL - Atma Murni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
Soft Skill-based Metacognitive Learning (SSML) and Metacognitive Learning (ML) demandthe students to plan, monitor, and evaluate their learning process and activity in solving problems. Thisstudy is a quasi-experiment with pre-test and post-test design. The aim of this research is to know the enhancement of Junior High School students’ abilities in mathematical representation ability (MRA).The population in this study is the students of Junior High School in Pekanbaru city. The sample consistof 202 students, 104 of them are from the high-level school, and 98 students are from the middle-levelschool. The instruments used in this study are mathematical prior knowledge (MPK) test, MRA test,instruction observation papers, students journal about the lesson, and the guideline for the interview.The data was analyzed using t-test, one-way ANOVA and two-way ANOVA. The result of dataanalysis indicates that: (1) overall, the enhancement of students’ MRA with SSML and ML approachsignificantly is higher than those with conventional learning (CL); (2) there is no interaction between thelearning approach (SSML, ML, and CL) with the school level (high and middle) toward the enhancementof MRA; (3) there is an interaction between the learning approach with MPK toward the enhancementof MRA.Keywords: mathematical representation ability, soft skill-based metacognitive learning.